1999
DOI: 10.4141/a98-074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sainfoin on in vitro digestion of fresh alfalfa and bloat in steers

Abstract: . 1999. Effect of sainfoin on in vitro digestion of fresh alfalfa and bloat in steers. Can. J. Anim. Sci. 79: 203-212. The effects of sainfoin (Onobrychis viciifolia) on digestion of alfalfa (Medicago sativa) were investigated in vitro and in vivo. Fresh alfalfa and sainfoin were incubated in an artificial rumen (Rusitec) in ratios of 100:0, 75:25, 50:50, 25:75 and 0:100 (as-fed). Disappearances of dry matter and N from sainfoin were 77 and 65% of those from alfalfa, respectively. Protease and endoglucanase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
3
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 49 publications
6
85
3
5
Order By: Relevance
“…S25 5 S0). Other beneficial effects of feeding sainfoin forage in association with lucerne, but not studied in this experiment, include a reduction in incidences of bloating (McMahon et al, 1999). More research should be carried out in order to identify other factors related to CT that could lead to variations in the effect of CT on the feed value of forage mixtures (content, structure and biological activity of CT, leaf/stem ratio, variety, preservation method and environmental conditions; Theodoridou et al, 2011 and.…”
Section: Intestinal Digestibilitymentioning
confidence: 98%
See 1 more Smart Citation
“…S25 5 S0). Other beneficial effects of feeding sainfoin forage in association with lucerne, but not studied in this experiment, include a reduction in incidences of bloating (McMahon et al, 1999). More research should be carried out in order to identify other factors related to CT that could lead to variations in the effect of CT on the feed value of forage mixtures (content, structure and biological activity of CT, leaf/stem ratio, variety, preservation method and environmental conditions; Theodoridou et al, 2011 and.…”
Section: Intestinal Digestibilitymentioning
confidence: 98%
“…These results suggested that the tannin-protein complexes formed in the rumen may not be fully dissociated post-ruminally (Barry and McNabb, 1999). Moreover, according to McMahon et al (1999), although sainfoin did not completely eliminate bloat in cattle grazing alfalfa-based pastures, there is evidence that sainfoin will reduce the incidence of bloat in grazing cattle if it accounts for at least 15% DM in the pasture.…”
Section: N Utilisationmentioning
confidence: 99%
“…However, when these animals graze on leguminous plants containing CT (for example Onobrychis viciifolia) this does not occur (Mangan, 1988;Aerts et al, 1999;Barry and McNabb, 1999;McMahon et al, 2000). The substitution of a small amount (approximately 10%) of ingested alfalfa DM by Onobrychis viciifolia provides unquestionable benefits in the prevention of bloat (McMahon et al, 1999 and2000). The problem of this strategy is, however, the low persistence of this plant species in mixed cropping with alfalfa.…”
Section: Bloat Preventionmentioning
confidence: 99%
“…Similarly, Waghorn and Jones (1989) demonstrated an absence of bloat in cows fed dock (Rumex obtusifolius) at 10% of dry matter while consuming a lucerne based diet. In addition bloat scores in steers have been reduced by feeding Sainfoin herbage (Onobrychris Viciifolia) at 10-20% dry matter (McMahon et al, 1999). Although it is possible to co-cultivate a bloat susceptible sward such as lucerne or clover with a CT containing plant such as Sainfoin, Lotus or Dock, consistent intakes of both plants by ruminants must be verified and production traits assessed before full recommendation to producers.…”
Section: Foam Production/bloat Controlmentioning
confidence: 99%